2017
DOI: 10.1007/s00134-017-5007-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of hospital infections by intervention and training (PROHIBIT): results of a pan-European cluster-randomized multicentre study to reduce central venous catheter-related bloodstream infections

Abstract: This study demonstrates that multimodal prevention strategies aiming at improving CVC insertion practice and HH reduce CRBSI in diverse European ICUs. Compliance explained CRBSI reduction and future quality improvement studies should encourage measuring process indicators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
62
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 38 publications
0
62
0
6
Order By: Relevance
“…Starting from the aspects related to our study of the correspondence between infection, section and pathogen, it is recommended the rapid, vigilant and targeted application of HAI prevention and control strategies for reducing infections in intensive care units [30][31][32][33][34][35], of surgical infections in the pre-, intra-and post-operative phase [36][37][38], reduction of urinary catheter infections [39][40][41], reduction of intravascular catheter infections [42,43], respectively, reduction infections with Clostridioides difficile [44].…”
Section: Discussionmentioning
confidence: 99%
“…Starting from the aspects related to our study of the correspondence between infection, section and pathogen, it is recommended the rapid, vigilant and targeted application of HAI prevention and control strategies for reducing infections in intensive care units [30][31][32][33][34][35], of surgical infections in the pre-, intra-and post-operative phase [36][37][38], reduction of urinary catheter infections [39][40][41], reduction of intravascular catheter infections [42,43], respectively, reduction infections with Clostridioides difficile [44].…”
Section: Discussionmentioning
confidence: 99%
“…PROHIBIT evaluated the effectiveness of two evidence-based CRBSI reduction strategies in intensive care units (ICUs) across 14 hospitals in 11 European countries. The trial demonstrated that these interventions could improve process indicators and reduce CRBSI incidence densities 28. InDepth used a longitudinal qualitative case study design, gathering data from 6 of the 14 hospitals in the trial.…”
mentioning
confidence: 99%
“…Las prácticas como Higienización de las Manos (HM) y cuidados con catéteres son significativas en el proceso de atención al paciente y prevención de daños. Un estudio multicéntrico realizado en las UCI europeas demostró que la HM redujo, la incidencia de infección en la corriente sanguínea asociada al catéter venoso central, de 2,4/1.000 pacientes/día a 0,9/1.000 pacientes/día (p<0,0001) (2) . Entretanto, todavía hoy, se observa un contexto caracterizado por la ocurrencia de sucesivos daños provenientes de la práctica asistencial, que llevan al surgimiento de un vacío entre el cuidado que el paciente debería recibir y aquel que es realizado (3) .…”
Section: Introductionunclassified